2019
DOI: 10.1055/s-0039-3399539
|View full text |Cite
|
Sign up to set email alerts
|

Normal Hearing Function in Children Prenatally Exposed to Zika Virus

Abstract: Introduction The association between prenatal Zika virus infection and hearing alterations in offspring has been the object of some studies, although few have assessed children without microcephaly. However, a current trend to include prenatal Zika virus exposure in the group of risk indicators for hearing loss is noted. Objective To present a series of 27 children prenatally exposed to the Zika virus submitted to multiple hearing assessments over time. Methods A cohort of children born to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Hearing impairment can occur in ZIKV-exposed children, but it is not a frequent manifestation. In a study made in Pernambuco in 2015, from 104 microcephalic children positive for ZIKV infection, hearing impairment was detected only in the two (12%) with the most severe microcephaly case [ 30 ]. Sensorineural hearing loss was described in another study, with 5 out 70 ZIKV-exposed children detected [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hearing impairment can occur in ZIKV-exposed children, but it is not a frequent manifestation. In a study made in Pernambuco in 2015, from 104 microcephalic children positive for ZIKV infection, hearing impairment was detected only in the two (12%) with the most severe microcephaly case [ 30 ]. Sensorineural hearing loss was described in another study, with 5 out 70 ZIKV-exposed children detected [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mosquito-borne pathogen is able to pass through the placental barrier to infect the fetus and create developmental problems ( Almeida et al, 2020 ; Cugola et al, 2016 ). The incidence of birth defects is difficult to assess with lack of access to the RT-PCR equipment necessary to rule out the infection in affected areas ( Barbosa et al, 2020 ; Fandino-Cardenas, Idrovo, Velandia, Molina-Franky, & Alvarado-Socarras, 2019 ; Leal, Muniz, Caldas Neto, van der Linden, & Ramos, 2020 ). This problem could explain the wide range of hearing deficits assessed in different studies, which range from 0% to 68% of infected fetuses ( Barbosa et al, 2020 ; Fandino-Cardenas et al, 2019 ; Satterfield-Nash et al, 2017 ).…”
Section: Environmental Causes Of Congenital Hearing Lossmentioning
confidence: 99%
“…The incidence of birth defects is difficult to assess with lack of access to the RT-PCR equipment necessary to rule out the infection in affected areas ( Barbosa et al, 2020 ; Fandino-Cardenas, Idrovo, Velandia, Molina-Franky, & Alvarado-Socarras, 2019 ; Leal, Muniz, Caldas Neto, van der Linden, & Ramos, 2020 ). This problem could explain the wide range of hearing deficits assessed in different studies, which range from 0% to 68% of infected fetuses ( Barbosa et al, 2020 ; Fandino-Cardenas et al, 2019 ; Satterfield-Nash et al, 2017 ). Another explanation could be the presence of different strains of ZIKV with different levels of aggressiveness ( Russo, Jungmann, & Beltrao-Braga, 2017 ).…”
Section: Environmental Causes Of Congenital Hearing Lossmentioning
confidence: 99%
“…Early evidence 9 has shown that prenatal exposure to ZIKV infection is associated with sensory-neural hearing loss. In general, its effect on the infant population has been well studied, 10 and in 2019, the Joint Committee on Infant Hearing inserted prenatal exposure to ZIKV as a risk factor for hearing loss. 11 This report provided strong evidence of the relationship of ZIKV with early hearing impairment and suggested follow-up beyond the pediatric age group.…”
Section: Introductionmentioning
confidence: 99%